Estimation of Inter Iliac Crest Distance by Ulna Length Measurement for Reference in Reduction of Pelvic Fractures - Pisuitthanakan, MD, Satapong; Suwanno, MNS, RN, APN, Juk; Tongtaluang, RN, Pattarawan (Journal of Southeast Asian Orthopaedics, 2022)
Objective: To determine inter iliac crest distance (IICD) by measurement of ulna length (UL) for reference in reduction of pelvic fractures (APC II). Materials and Methods: A cross sectional study was done among 325 healthy participants. They were enrolled and stratified into two groups according to gender. UL and IICD of each participants were measured and recorded in centimeters. R-program was used for the statistical analysis. Pearson correlation was tested. Simple and Multiple linear regression model were estimated to predict dependent factors affecting IICD. Results: The correlation between UL and IICD was 0.31 (P-value=0.001). The univariate equation was IICD=13.66+0.57(UL), R2 adjusted=0.10. The multivariate equation was IICD=13.51+0.30(UL) + 0.08(BW) + 0.05(Age), R2 adjusted=0.26, (BW=body weight). Conclusion: This is the first estimation of IICD by measurement of UL for reference in reduction of pelvic fracture (APC II). Because of low correlation, using this numeric assessment should be cautiously applied in clinical practice.